Czech Republic : Report on Observance of Standards and Codes-Fiscal Transparency Module-Update. (IMF Staff Country Reports; Country Report ;, 2003)
The Czech government has made further progress in improving fiscal transparency that was already high by international standards. The measures implemented to broaden the coverage of general government data have been commended. Improved reporting on fiscal risks, including those arising from contingent liabilities, has been welcomed. However, greater effort is needed to improve the public availability of fiscal data and to maintain regular tax expenditure reports. Ensuring appropriate standards for audit and fiscal discipline at the subnational level is critical.